A collaborative approval process for accessing sensitive data. (15th June 2007) - Peyton, Liam; Hu, Jun; Liu, Hao; Al-Saleh, Mansour; , Abdulmotaleb El Saddik
A collaborative environment to improve and streamline approval processes online is presented. A scenario for approving requests to access sensitive medical data records for research purposes from a medical data warehouse at a teaching hospital is used to illustrate the special requirements needed for collaborative approval processes. The architectural framework to support such processes is defined. It includes support for collaborative signatures, a service-oriented architecture to integrate security mechanisms, policy-based control to address privacy issues and categorisation and anonymisation of data along multiple dimensions to control access within a collaborative environment.